Qādiyān se Isrā̓īl tak : Bar̤tānvī aur Saihūnī sāmrāj aur Qādiyāniyoṉ ke bāhamī gahre ravābi̤t va taʻalluqāt - Samīʻulḥaq (Mu̓tamirulmuṣannifīn)
Critical study of the Ahmadiyya movement from the beginning of the 20th century.